2012
DOI: 10.14701/kjhbps.2012.16.3.93
|View full text |Cite
|
Sign up to set email alerts
|

Extrahepatic recurrence of hepatocellular carcinoma after curative hepatic resection

Abstract: Backgrounds/AimsThis study was designed to compare the recurrence patterns after curative hepatectomy, to compare the prognosis according to the initial site of metastasis, and to investigate the independent predictive factors associated with extrahepatic recurrence in hepatocellular carcinoma (HCC) patients after curative hepatectomy.MethodsFrom January 2000 to July 2009, 307 patients underwent curative hepatectomies for HCC at our institution; 152 patients showed recurrences. Patients were divided into 2 gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 16 publications
(20 reference statements)
1
13
0
Order By: Relevance
“…Byeon et al . reported that the preoperative AFP level was an independent risk factor for EHM ( P = 0.014) after a curative resection of HCC . Biologically, AFP has been reported to promote liver cancer growth and progression .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Byeon et al . reported that the preoperative AFP level was an independent risk factor for EHM ( P = 0.014) after a curative resection of HCC . Biologically, AFP has been reported to promote liver cancer growth and progression .…”
Section: Discussionmentioning
confidence: 99%
“…20 Byeon et al reported that the preoperative AFP level was an independent risk factor for EHM (P = 0.014) after a curative resection of HCC. 7 Biologically, AFP has been reported to promote liver cancer growth and progression. 21 Overexpression of AFP facilitates invasion and distant metastasis of HCC by upregulating the expression of metastasis-related proteins and activating the PI3K/AKT signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To improve the treatment outcomes and prognosis, predicting distant metastasis of HCC with PVTT is crucial. Variables such as high pretreatment platelet counts, numerous or large tumors, microvascular invasion, incomplete capsulation and high preoperative AFP are significantly associated with distant metastasis in HCC (18)(19)(20)(21); however, prediction models for the metastasis of HCC with PVTT are not currently available, to the best of our knowledge. In the present study, commonly accessed clinical and biochemical parameters were used to screen the risk factors significantly associated with the distant metastasis of primary HCC with PVTT to establish a convenient early warning system for distant metastasis.…”
Section: Discussionmentioning
confidence: 98%